Diachronic genre analysis: patterns of rhetorical organization in academic book reviews - Carvalho, Jorge Luis Queiroz (Revista da ABRALIN, 2020)
This study investigates vestiges of change and traces of permanence in academic book reviews produced between the 20th and 21st centuries. To this end, it aims to analyze the more frequent rhetorical moves in academic book reviews published between 1953 and 2015. The diachronic analysis covers a time continuum of 62 years which we divided in three generational phases: a) 1953-1970; b) 1971-2000; and c) 2001-2015. The division was based on the methodological parameters proposed by the Discursive Traditions paradigm. Each phase consists of 15 texts, adding up to a total of 45 samples that were collected from Brazilian scientific journals in the field of Languages and Linguistics. Epistemologically, we are based on the studies of John Swales (1990; 2004), as well as those of Motta-Roth (1995), Araújo (1996) and Bezerra (2001) to support the analysis of the rhetorical organization of reviews. In order to instrumentalize the diachronic analysis of genres, we found support in the works of Coseriu (1980), Zavam (2009), Castilho da Costa (2010) and other scholars in the already mentioned field of Discursive Traditions. The results have indicated four rhetorical moves present in the reviews: introducing to the book, summarizing the content, evaluating the book and issuing a final opinion. Those moves are divided in 16 rhetorical steps and their frequency and execution forms show traces of variation in each generational phase.